From an antique land: an introduction to ancient Near Eastern literature - Ehrlich, Carl S. (Rowman & Littlefield, 2009)
Sumerian literature / Gonzalo Rubio -- Egyptian literature / Susan Tower Hollis -- Akkadian literature / Benjamin R. Foster -- Hittite literature / Gary Beckman -- Canaanite literature / Wayne T. Pitard -- Hebrew/Israelite literature / Carl S. Ehrlich -- Aramaic literature / Ingo Kottsieper